Modeling of short-pulse child-langmuir law - Zhang, Peng (2009)
This report concentrates on the development of ID short-pulse space-charge-limiting (SCL) models for the classical, weakly relativistic and quantum regimes. Here, we are interested in the electron flows in the planar configuration at the space-charge limit. The effects of the finite pulse length of a SCL electron pulse emitted from a planar diode for a wide range of applied voltage, gap spacing, and pulse duration have been investigated. The results from the analytical short-pulse models in the classical and relativistic regimes are consistent with particle-in-cell (PIC) simulations. The transit time of the electron flows across a gap in various regimes (classical, relativistic, quantum) has also been formulated in analytical form. In addition, ID short-pulse models of classical and relativistic SCL law in a drift space is developed. And a selfconsistent model of transition from field emission to short-pulse classical CL law is also presented.